Long term outcomes after incident diabetic foot ulcer: Multicenter large cohort prospective study (EDI-FOCUS investigators) epidemiology of diabetic foot complications study: Epidemiology of diabetic foot complications study. (April 2020) - Rastogi, Ashu; Goyal, Ghanshyam; Kesavan, Rajesh; Bal, Arun; Kumar, Harish; Mangalanadanam,; Kamath, Priyatham; Jude, Edward B.; Armstrong, David G.; Bhansali, Anil
Highlights: Risk of amputation and mortality after an incident first neuropathic foot ulcer in Asian Indian population is not known. Prospective assessment over 14 years suggests that incident neuropathic foot ulcer is associated with more than seven times increase risk of mortality compared to those who do not develop foot ulcer despite of similar age and duration of diabetes. Prevalent nephropathy and incident amputation following diabetic foot ulcer and not glycemic control or prior coronary artery disease predicted mortality amongst patients with diabetic foot ulcer. Abstract: Aims: This long-term prospective study evaluated limb amputation and mortality after the first neuropathic diabetic foot ulcer (DFU). Methods: A total of 2880 patients with neuropathic DFU (DFU group) and a similar number of patients of diabetes without DFU (nDFU) matched for age and diabetes duration were prospectively assessed at five referral-centers over 14 years. Pre-defined outcome was death during follow-up. Various diabetic co-morbidities and amputation were assessed as mortality predictors. Results: Overall, 501 (17.4%) patients in DFU group died compared to 89 (3.1%) (p < 0.01) in nDFU group during a median follow-up of 7(1–14) years. The 5- and 10-year mortality was 22% and 71% in the DFU group with a median survival of 7.72 (7.37–8.08) years compared to 3% (p < 0.01) and 5% (p < 0.01) and survival of 12.6 (10.5–12.7) years (p < 0.001) in nDFU group. 29.3% patients had limb amputations. The mortality risk was independent of glycemic control [OR 1.03 (0.80–1.32; p = 0.83)]. However, diabetes duration > 10 years [OR 1.31(1.02–1.70, p = 0.035)], nephropathy [OR 1.47 (1.04–2.09, p < 0.030)], minor 1.85 (1.40–2.44; p < 0.001) or major amputation 2.96 (2.01–4.34, p < 0.001)] predicted mortality. Conclusions: Every one-in-three individual with neuropathic DFU has amputation and every sixth individual has an early demise. Prevalent nephropathy and incident amputation following DFU predicts mortality.